The development of conceptual model for improving sustainable building construction implementation - Mat Russ, Nazirah; Hanid, Mahanim; Kho, Mei Ye (The Mattingley Publishing Co., Inc., 2020)
Ongoing discussion about sustainable building construction problems such as high initial cost caused by ―green cost premium‖ supported by long-term and uncertain of return on investment (ROI) as well as long-term and low profitability, lead to passive involvement of construction practitioners to construct sustainable building even many benefits are well documented. Previous research finding revealed that, most of the construction practitioners are not willing to spend more just to implement sustainability in their project and some of them has no long-term interest in operating or leasing the buildings. Hence, the question arises on ―how can this issue be resolved?‖. Therefore, this study presents a conceptual model aiming at reducing the initial cost of sustainable building construction project with the hope that this will encourage construction practitioners to invest in sustainable building construction project. Based on the analysis of existing literature (e.g.: conference paper, journal article) there are 19 cost reduction methods, that classified into six elements:technical approach, motivation, design management, project team characteristic, practical approach and management innovation. As there are limited studies conducted on methods to reduce sustainable building construction cost, the authors decided to gather an information on methods to reduce initial project cost not limited to sustainable building construction and in various industries. The components of this conceptual model were constructed based on theories and empirical evidence relating to cost reduction at which, the authors combine and conceptualized them into input-process-output (IPO) model to produce the proposed conceptual model of this study. At the end of this stage, the authors found 9 constructs with 2 associations.